Penguasaan Konsep dan Berpikir Kritis Siswa Kelas IV pada Materi Sifat-sifat Cahaya melalui Pembelajaran POE Berbantuan Google Meet - Setia, Ayu; Jayadinata, Asep Kurnia; Syahid, Aah Ahmad (Jurnal Pena Ilmiah, 2021)
Mastery of concepts and critical thinking of elementary school students need to devole in order to understand the phenomena that often occur in the surrounding environment. Mastery of good concepts can encourage students to think critically. But currently the ability to master concepts and critical thinking of elementary school students is still low. The research aims to find out how the implementation of google meet-assisted POE learning on light properties, as well as how to master concepts and critical thinking of students after carrying out google meet-assisted POE learning. The researchers used qualitative descriptive methods. The population in this study is the entire elementary school grade IV in South Sumedang sub-district. The sample used is one of the elementary school located in South Sumedang, namely SDN Pakuwon I in IVA class through Purposive Sampling technique. Instrument used in the form of observation sheets of teacher performance and student activity, student evaluation results, and interviews. From the results of the research obtained that the implementation of POE learning in the class of IVA SDN Pakuwon I is in the category of very good, it can be seen from the cooperation between teachers and students when carrying out POE learning assisted by google meet. Then the mastery of concepts and critical thinking of IVA grade students are in the good category because it has reached the minimum threshold.